Adoption pattern of fertiliser technology among farmers in the ecological zones of southwestern Nigeria: a Tobit analysis - Bamire, A.; Fabiyi, Y.; Manyong, Victor M. (Commonwealth Scientific and Industrial Research Organisation, 2002)
Using data from a survey of farm operators in two major ecological zones of Osun State in south-western Nigeria, this paper empirically evaluates the determinants of farmers' fertiliser adoption decisions and the intensity of use of the technology using a Tobit regression model. With a multi-stage sampling technique, data were collected with the aid of a structured questionnaire drawn on 180 respondents in the agroecological zones of the State. This was complemented with focus group discussions in each of the zones. Data were analysed using descriptive statistics and Tobit regression techniques. A majority of the respondents in the study area are young and energetic but with low literacy level. Mixed cropping practice was dominant and farming was at a small scale. Large proportions of respondents had extension contact and were members of associations. Tobit estimates show that farmers' fertiliser adoption decisions vary with agroecological location, and a decomposition of the elasticities calculated at the means of the variables revealed that farmers' probability of adoption and non-adoption accounted for more of fertiliser technology response than did the use intensity, given adoption. Thus, a policy that increases the quantity of fertiliser made available to farmers in the right form and time will encourage the adoption and use of the technology in improving the land resource potential.